Margójegyzetek a regionális politikához - Nemes Nagy, József (Tér és Társadalom, 1992)
The regional tendencies of the Hungarian economy are ruled by the processes of differentiation these days. The duality of the capital city and the rural areas are becoming even more emphasized, and the differences between the Western and the Eastern parts of the country, and the urban and rual areas are increasing. Tendencies of differentiation appeared already in the early 1980s, with the spread of non-agricultural cooperative enterprises. These semiprivate companies, that were srongly related both to the state companies and the cooperatives, were concentrated in the capital city, in its agglomeration, in bigger cities, near the Lake Balaton, and in the more prosperous Western parts of the country. This fairly polarized spatial structure was further polarized by privatization starting after the transformation, the influence of Western capital, and the concentration of new economic associations and joint ventures in the very same regions. The Northern and Eastern parts of the country are in real crisis. There is high unemployment, economic transformation goes on very slowly, and the profitability of the economy is very low. The middle part of the country, which used to be the most developed region (after the capital city) and was characterized by heavy industry is a region in absolute depression now. In reality, there is no single positive pole, traction area, zone absorbing labour in the country, as the capital city and the Western parts are in better situation than the average only if their relative situation is taken, because the symptoms of crisis are widespread in these regions as well. The organizational and property transformation of the economy goes on amidst the conditions of economic recession. In 1991, the GNP decreased by about 10%, and further decline can be expected in 1992 as well, as the productive and social investments have decreased considerably. In the middle of 1992, the number of unemployed reached 600 000, namely 10%, and is increasing unstoppably. In the Eastern part of the country, the unemployment rate is 20%. The collapse of the Eastern markets, and the lasting processes of new ownership and property relations plunged the agriculture, and consequently the agricultural zones of the country, and the rural settlements in general into a deep crisis. At present, regional and settlement polarization of the country is one of the most important dimensions of social differentiation, and of the increase of income and property differences. Effective regional policy cannot counterbalance these processes. There is no comprehensive regional development concept. The institutional systems of a regional policy meeting the new conditions have not been developed yet, and the drafting of the new regional development act has been going on for two years, but it is not expected to be passed in 1992. Regional development and regional policy belong to nowhere both in the government and the local authorities. Uniform governmental management of regional policy is unsolved, and the spheres of influence are divided among several ministries, and consequently the contradictions in authority and coordination are quite frequent. Though the financial resources aiming to ease the local crisis situations are increasing, their volume is insufficient as compared to the size of the problems, their use is fragmented and does not fit properly into the concept, thus their influence is very little. A kind of medium regional levei, that could have some role in regional policy as well, is missing from the system of local governments. There is no regional coordination in economic development. Due to the missing institutions – the responsible governing body of regional policy, the organizations managing regional econimic development – further increases in regional differences (increasing duality between the urban and rural areas, differences between the Eastern and the Werstern parts of the country, polarization between the towns and the villages) can be expected as a consequence of the spontaneous processes of developing a market economy.